The Molecular Detection of EBV Among Hodgkin and Non-Hodgkin Lymphoma in Iraqi Patients - Saleh, Aya Raad (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Objective: The study amied to detect the molecular pattern of Hodgkin lymphoma and non-Hodgkin lymphoma (NHL) in Iraqi patients and identifying the most common kind of both among the female and male Iraqi patients . Epstein-Barr virus (EBV) infection is closely associated with many subtypes of malignant lymph nodes of both Hodgkin and non-Hodgkin lymphoma. Two of the most common hematological malignancies in the world are NHL and HL. Having a variety of biological and clinical characteristics, it originates from lymph tissue. Method: 359 specimens ranging in age from 25 to 75 years were gathered from the pathology departments of Al _kadhymia teaching hospital/ hematology department. Our goal was to find out how common EBV is in NHL and HL. Result: The current study included 359 specimens (186 females and 173 males), which investigated the percentage of NHL in ladies was (35.1%), whereas HL's was (64.9%) . HL with (43.2%) was detected in males, while NHL was (57.8%) ,which represent a higher differences (P≤0.0001) between NHL and HL in female and male.